TESTING THE EFFECT OF LAYER THICKNESS ON THE ACCURACY AND PRECISION OF PRODUCTâS DIMENSION MANUFACTURED BY FDM 3D PRINTER - Jati Radityo, Satyo
Over the years, people need more and more complicated products/components. It is becoming common for companies to use 3D Printer to manufacture a prototype with a complicated design. The accuracy and the precision of the product’s dimension is usually the parameters that are considered to be important in the making of prototype using 3D printer. One of the many factors that affect accuracy and precision of the dimension significantly is layer thickness. Testing procedure to verify the effect of layer thickness on accuracy and precision of product’s dimension manufactured by 3D printer needs to be done. Before the testing for the effect of layer thickness on accuracy and precision of product can be started, the 3D printer’s movement need to be checked so that the obtained data is valid. Testing was done by printing three types of block, each with different variation. Each variation were printed by three different layer thickness, that is 0.15mm; 0.20mm; and 0.30mm. It is obtained that the product with 0.15mm layer thickness is the most accurate and the most precise, with 0.04mm dimension’s range and an average dimension’s error of 0.72%. Product with 0.20mm layer thickness has 0.08mm dimension’s range and an average dimension’s error of 0.76%. Product with 0.30mm layer thickness is the least accurate and the least precise, with 0.10mm dimension’s range and an average dimension’s error of 0.80%. From the testing, it is obtained that the smaller the layer thickness is, the better the accuracy and the precision of product’s dimension. It is to be expected that this project encourage further study about 3D printer.